Design and Development of an Automation Device for Free-Fall Motion Experiments Based on a Web-Remote Laboratory - Annovasho, Jhelang; Yuliani, Hadma; Ramadhan, Panji; Rudianto, Rahmat (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2025)
Design and Development of an Automation Device for Free-Fall Motion Experiments Based on a Web-Remote Laboratory. This study aims to develop an automated free-fall experiment device integrated with a web-remote laboratory system. The web-remote laboratory is a real laboratory that can be controlled and displays results remotely through an internet connection. The research follows the Design and Development Research (DDR) methodology, which encompasses several stages: problem identification, objective formulation, system design and development, system testing, evaluation, and refinement. A domain hosting service was employed to deploy the web server, providing greater flexibility and ease in developing control interfaces compared to applications such as Blynk and ThingSpeak. The design and development process addressed both hardware-mechatronic and software components. The software was implemented on the microcontroller and the webserver to enable seamless integration. Testing was conducted in two phases, which informed product evaluation and subsequent refinements. The resulting device supports automation, features fully functional mechatronic systems, ensures optimized sensor sensitivity, facilitates user-friendly control via a web browser, and provides accurate calculations of gravitational acceleration during free-fall experiments. Despite its strengths, the ESP8266 microcontroller was suboptimal for applications requiring high sensitivity. Additionally, the web interface lacked multi-user support. These limitations present opportunities for further development and optimization of the device. Overall, the findings of this study provide a practical and innovative solution to enhance student engagement in laboratory activities, particularly in educational settings with limited access to physical laboratory equipment.